Effect of hydration with Ringer’s solution submitted to magnetic field in an experimental model of hepatic ischemia-reperfusion injury in rats - Freire, Juliana Mendonça; Souza, Jeovana Pinheiro Fernandes de; Azevedo, Italo Medeiros; Azevedo, Fabio Medeiros de; Carriço, Artur da Silva; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2018)
Purpose: To evaluate the effect of hydration with Ringer's solution submitted to magnetic field in experimental model of hepatic ischemia/reperfusion in rats. Methods: Wistar rats weighing 389.58±46.88g were randomly allocated into 2 groups: control group (n = 6) - Hepatic ischemia/reperfusion and hydration with Ringer's solution; and test group (n = 6) - Hepatic ischemia/reperfusion and hydration with Ringer submitted to magnetic field of 20 mT during 2 hours. After anesthesia with ketamine 70 mg/kg and xylazine 7 mg/kg i.p., the animals were weighed and operated by aseptic technique. The ischemia of the median and left liver lobes was induced for 30 minutes using a vascular clip. Then, i.v. hydration with 3 ml of Ringer in the control group, and 3 ml of magnetized Ringer’s solution in the test group. After 24 hours, blood sample and fragment of the left liver lobe were collected for the determination of AST, ALT, ALP and albumin levels, and histopathological examination. Results: There was no significant difference in comparison of the rats weight loss, biochemical measurements and histopathological scores between the groups (p>0.05). Conclusion: The hydration with Ringer's solution submitted to magnetic field after hepatic ischemia/reperfusion in rats did not alter liver function tests neither histopathological scores, comparing with the control group.